Innovative CO2-NBs-assisted ultrasonication for the phytochemical extraction of peanut (Arachis hypoga) shells: Synthesis and characterization of CO2-nanobubbles - Nayyar Iqbal; Miral Javed; Ramy M. Khoder; Areej Areej; Renyu Zheng; Shanbai Xiong; Ibrahim Khalifa; Hassan Barakat; Youming Liu (Ultrasonics Sonochemistry)
This study was designed to obtain the maximum extraction yield of peanut shell (PS) polyphenols using a novel carbon dioxide nanobubbles (CO2-NBs) assisted ultrasonic extraction method. CO2-NBs were generated in distilled water with a self-developed high-pressure nano-jet homogenization method and characterized by size, zeta potential and transmission electron microscopy (TEM). The obtained nanobubble’s mean size and zeta potential were 229.96 ± 17.44 nm and −15.9 ± 1.27 mV, respectively. Later, these CO2-NBs, combined with ultrasonic method, were used for the extraction of polyphenols, achieving the highest polyphenol content (3619.21 ± 113.07 µg GAE/mL) as compared to ultrasonic extraction (2914.69 ± 145.45 µg GAE/mL) and conventional extraction (2340.11 ± 80.02 µg GAE/mL). Response surface methodology (RSM) provided optimization parameters, including ultrasonic power of 358.76 W, surfactant concentration of 4.54 %, and extraction time of 41.41 min. HPLC analysis identified distinct peaks corresponding to polyphenolic compounds such as gallo-catechin, catechin gallate, resveratrol, and luteolin, confirming their presence and concentrations in the peanut shell extract (PSE). Scanning electron microscopy (SEM) revealed significant structural disruption and increased porosity in peanut shell powder, supporting the enhanced extraction of polyphenols through CO2-NBs-assisted ultrasonic extraction process. This research establishes theoretical and practical foundation for generation of CO2-NBs and CO2-NBs ultrasonic extraction technology to efficiently extract polyphenols from waste PS, thereby enhancing the extraction efficiency of valuable compounds for use in functional food products and promoting sustainable practices in food industry.